1992
DOI: 10.1073/pnas.89.14.6462
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of exoprotein expression in Staphylococcus aureus by a locus (sar) distinct from agr.

Abstract: A single insertion of transposon Tn917LTV1 into the chromosome ofa Staphylococcus aureus Cdinical isolate, strain DB, resulted in a pleiotropic effect on the expression of a number of extraceilular and cell-wall-as ted proteins. Detailed comparison ofphenotype associated with the mutant, 11D2, and the parent, DB, indicted that the chromosomal locus inactivated as a result of transposon mutagenesis differs from the S. aureus accessory gene regulator locus (agr). In particular, the expression of a-hemolysin, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
386
2
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 365 publications
(398 citation statements)
references
References 20 publications
8
386
2
2
Order By: Relevance
“…S. aureus causes a number of infections ranging from superficial skin abscesses to life-threatening systemic diseases (e.g., toxic shock syndrome and osteomyelitis) (17,25,38). The synthesis of a variety of extracellular and cell surface proteins involved in the pathogenesis of S. aureus has been shown to be controlled by at least two global regulatory elements, agr and sar (4,5,12,13,23,26,27,29,32,34). The agr system is the best characterized of these elements and responds to environmental stimuli, thereby resulting in the elevated synthesis of extracellular toxins with a concomitant decrease of the synthesis of surface proteins.…”
mentioning
confidence: 99%
“…S. aureus causes a number of infections ranging from superficial skin abscesses to life-threatening systemic diseases (e.g., toxic shock syndrome and osteomyelitis) (17,25,38). The synthesis of a variety of extracellular and cell surface proteins involved in the pathogenesis of S. aureus has been shown to be controlled by at least two global regulatory elements, agr and sar (4,5,12,13,23,26,27,29,32,34). The agr system is the best characterized of these elements and responds to environmental stimuli, thereby resulting in the elevated synthesis of extracellular toxins with a concomitant decrease of the synthesis of surface proteins.…”
mentioning
confidence: 99%
“…Inactivation of this locus by Tn917LTV1 insertion has resulted in decreased expression of several extracellular (e.g., ,B-hemolysin) and cell wall proteins (3). Phenotypic, Southern blot, and genetic mapping analyses indicated that this locus is distinct from agr and xpr (3,4). Using the DNA sequence flanking the Tn917LTV1 insertion as a probe, we have subsequently cloned and sequenced the sar gene that is involved in the regulation of exoprotein synthesis., Additional transcriptional and phenotypic studies revealed that this sar gene is necessary for the optimal expression of agr.…”
mentioning
confidence: 99%
“…We recently reported an additional locus in S. aureus, designated sar, that is involved in the regulation of exoproteins (3). Inactivation of this locus by Tn917LTV1 insertion has resulted in decreased expression of several extracellular (e.g., ,B-hemolysin) and cell wall proteins (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations